2022
DOI: 10.3389/fped.2022.898463
|View full text |Cite
|
Sign up to set email alerts
|

The Omicron variant of concern: The genomics, diagnostics, and clinical characteristics in children

Abstract: Since WHO announced the COVID-19 pandemic in March 2020, SARS-CoV-2 has undergone several mutations, with the most recent variant first identified in South Africa in November 2021, the SARS-CoV-2 variant of concern (VOC B.1.1.529) named by WHO as Omicron. To date, it has undergone more mutations compared to previous SARS-CoV-2 variants, particularly, in the S gene that encodes the spike protein, which can cause S gene target failure in some PCR kits. Since its discovery, the Omicron variant has caused a sharp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
1
28
0
1
Order By: Relevance
“…Like other RNA viruses, SARS-CoV-2 continuously mutates, resulting in the emergence of SARS-CoV-2 variants, which may have different pathological effects [ 74 ]. The variants B.1.617.2 (Delta), B.1.466.2, B.1.470, B.1.1.7 (Alfa), B.1.351 (Beta), P.1 (Gamma), P.2 (Zeta), and B.1.1.529 (Omicron) are among the most notable SARS-CoV-2 variants due to their potential to enhance biological threats [ 75 , 76 , 77 , 78 ]. Four mutations (N501Y, 69-70del (69/70 deletion), K417N, and E484K) in the spike protein may be linked to the potential biological effects of some of these variants.…”
Section: Detection and Quantification Of Sars-cov-2mentioning
confidence: 99%
“…Like other RNA viruses, SARS-CoV-2 continuously mutates, resulting in the emergence of SARS-CoV-2 variants, which may have different pathological effects [ 74 ]. The variants B.1.617.2 (Delta), B.1.466.2, B.1.470, B.1.1.7 (Alfa), B.1.351 (Beta), P.1 (Gamma), P.2 (Zeta), and B.1.1.529 (Omicron) are among the most notable SARS-CoV-2 variants due to their potential to enhance biological threats [ 75 , 76 , 77 , 78 ]. Four mutations (N501Y, 69-70del (69/70 deletion), K417N, and E484K) in the spike protein may be linked to the potential biological effects of some of these variants.…”
Section: Detection and Quantification Of Sars-cov-2mentioning
confidence: 99%
“…All the Omicron subvariants share eleven common mutations in the RBD of the spike protein, which is responsible for enhanced transmission, evasion, antibody neutralization, and RNA expression ( 76 ). Omicron variant can evade neutralizing antibody (NA) and weaken existing COVID-19 vaccine protection, but vaccine boosters can boost immunity ( 77 ) and improve the efficacy by 12-35 fold ( 78 ). However, most of the neutralizing monoclonal antibodies which are approved by the FDA for the treatment of SARS‐CoV‐2 variants, are ineffective against the Omicron variant except for Sotrovimab, and recent studies revealed that the Omicron BA.2 is also resistant to Sotrovimab ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that BA.3 has 34 mutations, including R216, which is a unique mutation. Further, compared to BA.1, BA.3 showed a higher capability to transmit among people [12]. Our literature review will thoroughly explain the current state of Omicron emergence, particularly by comparing different omicron subvariants, including BA.2, BA.1, and BA.3.…”
Section: N Introductionmentioning
confidence: 99%